Pengaruh Model Pembelajaran Numbered Head Together (NHT) Terhadap Hasil Belajar Ditinjau dari Motivasi Siswa dalam Pembelajaran PAI di SMPN 1 Simpang Alahan Mati - Masitah, Ilfah; Rahmi, Siska Yulia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research is motivated by the results of observations at SMPN 1 Simpang Alahan Mati where information was obtained that, when the teacher gave questions to students out of 27 only 5 students raised their hands, students were also found to be less concentrated in learning, and students who approached their friends next to them. This type of research uses a quantitative approach with a Quasi Experiment research method. The population in this study were all students of class VII at SMPN 1 Simpang Alahan Mati, the sampling technique used cluster random sampling. The data collection technique was through Tests and Questionnaires (Questionnaire). The test is carried out by giving a series of questions or other tasks to the subjects whose data is needed. The questionnaire or questionnaire is carried out by giving a collection of written questions to respondents to answer. The data analysis technique in this study was carried out by statistical tests (discriminatory power or T test). Before testing the hypothesis, a prerequisite test was carried out first, namely the normality and reliability tests. From the research at SMPN 1 Simpang Alahan Mati, it was concluded that the influence of the Numbered Head Together (NHT) learning model on learning outcomes in highly motivated students, namely in the t-test with a significant level of 2 tailed has a value of less than 0.05, namely 0.039 indicating Ho is rejected and Ha is accepted. While the influence of the Numbered Head Together (NHT) learning model on learning outcomes in moderately motivated students, namely in the t-test with a significant level of 2 tailed has a value of less than 0.05, namely 0.002 indicating Ho is rejected and Ha is accepted. Then the influence of the Numbered Head Together (NHT) learning model on learning outcomes in highly motivated students, namely in the t-test with a significant level of 2 tailed has a value of less than 0.05, namely 0.022 indicating Ho is rejected and Ha is accepted